The effect of bone marrow mesenchymal stem cell-derived extracellular vesicles on bone mineral density and microstructure in osteoporosis: A systematic review and meta-analysis of preclinical studies - Ying Zhang; Xining Xu; Ximei Ren; Zhenghong Li (PLoS ONE, 2025)
Objective The treatment of osteoporosis is challenged by limited bone regeneration and side effects. Bone marrow mesenchymal stem cell-derived extracellular vesicles (BMSC-EVs) have gained widespread attention as a potential therapeutic approach. This study aims to evaluate the effects of BMSC-EVs on bone density, trabecular microstructure, and biomechanical properties in animal models of osteoporosis, providing evidence to support clinical translation and mechanism exploration. Methods A systematic search was conducted in the PubMed, Cochrane, Web of Science, and Embase (inception to January 2025) databases for preclinical studies on BMSC-EV intervention in osteoporosis models. A random-effects model was used to synthesize and analyze seven key parameters (BMD, BV/TV, Tb.N, Tb.Sp, Tb.Th, Ct.Th, and ultimate load-bearing capacity). Subgroup analysis was performed based on species (rats/mice), EVs engineering targets/methods, injection frequency, and treatment duration. The quality of the studies was assessed using SYRCLE’s risk of bias tool. Results The meta-analysis of 10 studies (355 animals) showed that, compared to the control group, BMSC-EV treatment significantly increased BMD, BV/TV, Tb.N, Tb.Th, Ct.Th, and ultimate load-bearing capacity, while reducing Tb.Sp in the osteoporosis model. A publication bias was found in the summary analysis for Tb.N. However, sensitivity analysis confirmed that all summary results were relatively stable. Conclusions Compared to the control group, BMSC-EV treatment demonstrated positive effects in increasing BMD, improving trabecular microstructure, cortical thickness, and biomechanical properties in the osteoporosis model. However, clinical translation still requires standardized EV characterization and preclinical safety assessments.